PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PENDEKATAN SAINTIFIK PADA MATERI EKOSISTEM KELAS VII SMP - Apriani, Suci; Fauziah, Yuslim; Arnentis, Arnentis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrack : Ecosystem is one of the material realeted to daily life. This research aims to develop a learners worksheet based on a scientific appoarch to the ecosystem material 7th Junior High School.This research was conducted in April-August 2017. The type of research is development research by using ADDIE model which done until development stage. There were three LKPD developed. Instrument used to collect data are students response questionnaires. The data were obtained from the development of LKPD based on the scientific appoarch on the 7th grade material ecosystem of the Junior High School which has been validated by 4 validators consisting of 2lecturers of biology education and 2 Junior High School teachers 1 Pekanbaru on desin aspect, pedagogic aspect, and content aspect. The revised LKPD is tested to university student, the average result of the university student respos on all LKPD was 3.17 score with good category (B). Then, tested to 7th grade student. The third mean LKPD has a score of 3.74 with a valid category. LKPD who obtained the highest score is LKPD 2 and 3 categorie, namely 3.75 valid. This can be seen in the scores obtained by LKPD 2 and 3 on each aspect.Keyword: Student’s Worksheet, Scientifik, Ecosystem